2011
DOI: 10.1177/1071181311551049
|View full text |Cite
|
Sign up to set email alerts
|

Pupil Dilation as an Index of Learning

Abstract: Physiological assessment of cognitive processes has become a topic of increased interest. The value of understanding and measuring brain function at work has the potential to improve performance. The emphasis of this paper is to discuss how pupil diameter can be applied to learning. The link between pupil diameter and task difficulty, or cognitive load, has been repeatedly demonstrated for the past 40 years. However there has been little work to date on measuring cognitive load during training or looking at ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…The approach direction of the subsequent test trial did not affect average pupil size during presentation of the mask, and no interactions were observed (all p > .05). The decrease in pupil size across experimental blocks during test trials and presentation of the mask is consistent with effects attributed to learning (Mueller et al, 2008;Sibley, Coyne & Baldwin, 2011). Furthermore, larger pupil size during different-direction trials as compared to same-direction trials may reflect the additional cognitive effort required by users of the configuration strategy to perform spatial transformations when the approach directions during training and test are not identical.…”
Section: Response Timesupporting
confidence: 68%
See 1 more Smart Citation
“…The approach direction of the subsequent test trial did not affect average pupil size during presentation of the mask, and no interactions were observed (all p > .05). The decrease in pupil size across experimental blocks during test trials and presentation of the mask is consistent with effects attributed to learning (Mueller et al, 2008;Sibley, Coyne & Baldwin, 2011). Furthermore, larger pupil size during different-direction trials as compared to same-direction trials may reflect the additional cognitive effort required by users of the configuration strategy to perform spatial transformations when the approach directions during training and test are not identical.…”
Section: Response Timesupporting
confidence: 68%
“…First, average pupil size decreased over the course of the experiment, which can be explained by learning effects and/or the transfer of task relevant information from working memory to long-term memory (Mueller et al, 2008;Sibley et al, 2011). Second, average pupil size was larger during different-direction trials compared to same-direction trials, which is thought to reflect the additional cognitive effort required by users of the configuration strategy to transform viewpoints when the approach directions during training and test did not match.…”
Section: Discussionmentioning
confidence: 98%
“…Physiological sensor data can provide information about a user's state in near-real time. For example, previous research has shown that an individual's mental effort correlates with pupil size [48,49] and heart rate variability [50]. Furthermore, eye gaze analysis can be used to assess where an individual is allocating attention (or failing to attend to), and therefore be employed to provide alerts and prevent errors in real time [51,52].…”
Section: A-tasc Predictive Modelmentioning
confidence: 98%
“…Then, the link between 155 attention and capacity was promoted [42]; where higher load on the working memory 156 showed a larger change in pupil dilation. Additionally, pupillary response has been 157 found to be an indicator of learning [34], where pupil diameter decreased with more 158 experience in a task. This understanding of pupil diameter changes has further been 159 employed as a robust cognitive load classifier [39].…”
mentioning
confidence: 99%